Respuesta :
Answer:
x=−27
Step-by-step explanation:
5(x+3)=4(x−3)
Step 1: Simplify both sides of the equation.
5(x+3)=4(x−3)
(5)(x)+(5)(3)=(4)(x)+(4)(−3)(Distribute)
5x+15=4x+−12
5x+15=4x−12
Step 2: Subtract 4x from both sides.
5x+15−4x=4x−12−4x
x+15=−12
Step 3: Subtract 15 from both sides.
x+15−15=−12−15
x=−27
Answer:
B
Step-by-step explanation:
Given
5(x + 3) = 4(x - 3) ← distribute both sides
5x + 15 = 4x - 12 ( subtract 4x from both sides )
x + 15 = - 12 ( subtract 15 from both sides )
x = - 27 → B